2008
DOI: 10.1007/s10764-008-9247-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Dung to Estimate Gorilla Density: Modeling Dung Production Rate

Abstract: There is an urgent need for information on western gorilla population sizes and distribution to improve present and plan future conservation actions. Researchers traditionally have estimated gorilla densities on the basis of nest counts despite demonstrated variation in nest production and decay rates. The variation may lead to large biases in estimates of gorilla abundance. We investigated the use of an alternate index of gorilla abundance, via defecation data collected from habituated gorillas at Bai Hokou, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 47 publications
0
48
0
1
Order By: Relevance
“…Pour ce dernier cas, le comptage de crottes a un certain potentiel, selon une étude récente à Bai Hokou qui montre que les crottes et les nids sont trouvés à une fréquence comparable (Todd et al 2008). Les comptages de crottes peuvent être réalisés de manière similaire aux comptages des nids sur des transects (méthodes ci-dessus) (Plumptre 2000 van Schaik et al 2005;Ancrenaz et al 2004a;Johnson 2005 dégradation des crottes de gorille sont sujettes à une énorme variation spatio-temporelle (Kühl et al 2007).…”
Section: Comptage Des Crottesunclassified
“…Pour ce dernier cas, le comptage de crottes a un certain potentiel, selon une étude récente à Bai Hokou qui montre que les crottes et les nids sont trouvés à une fréquence comparable (Todd et al 2008). Les comptages de crottes peuvent être réalisés de manière similaire aux comptages des nids sur des transects (méthodes ci-dessus) (Plumptre 2000 van Schaik et al 2005;Ancrenaz et al 2004a;Johnson 2005 dégradation des crottes de gorille sont sujettes à une énorme variation spatio-temporelle (Kühl et al 2007).…”
Section: Comptage Des Crottesunclassified
“…Secondarily, the ''known'' scientific observations are rife with variability. Dung pile production rate has strong associations with rainfall and feeding behavior and striking differences between age classes, varying from 2-11 piles a day (Todd et al, 2008). Once deposited, climate, environment, and fecal consumers affect sample longevity in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The large spatial scale and short duration of the fecal surveys was intended to reduce the likelihood of sampling individuals more than once. Although most researchers prefer to use nest detection over feces for primate population surveys, we analyzed feces to generalize our results to nonnesting species (Kü hl et al, 2008;Todd et al, 2008).…”
Section: Fecal Sampling Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…This species disperses seeds in a spatially and temporally bimodal pattern with more than 50% of seeds deposited at nest sites (Todd et al, 2008), which are preferentially installed in open habitats (Tutin et al, 1991;Rogers et al, 1998;Voysey et al, 1999;Petre et al, 2015a). Seedling growth is enhanced in tree fall gaps, even for shade tolerant species (Howe et al, 1985;Popma and Bongers, 1988 and references therein; Schupp et al, 1989), and a beneficial effect of deposition at gorilla nest sites was observed for three tree species at Lopé, Gabon (Tutin et al, 1991;Rogers et al, 1998;Voysey et al, 1999).…”
Section: Introductionmentioning
confidence: 92%